Malian Conflict: Underlying Causes and Implications, 2012 to 2017 - ODDIH, Mike C.; EMESIBE, Vincent Obiora (Socialscientia: Journal of Social Sciences and Humanities, 2022)
This paper examined the underlying factors behind the 2012 Malian crisis and its implications for the Sahel region. The data were collected through interviews complemented with literature. The paper employed Robert Cox’s Critical Theory and thematic method in its analysis. The findings indicate that the Tuareg-led northern Malians’ grievances borne out of long neglect and marginalisation by southern based government in Bamako are the dominant underlying causes of 2012 Malian crisis. The Malian situation calls for prompt redress through all inclusive government and functional autonomy to the northern Mali, state building, delivery of massive improvements in government services to the entire Malian citizens, but particularly to northern Malians. The peace process should be strengthened and its implementation decentralized.